Geographical distribution of Burkholderia pseudomallei in soil in Myanmar - Swe, MMM; Win, MM; Cohen, J; Phyo, AP; Lin, HN; Soe, K; Amorncha, P; Wah, TT; Win, KKN; Ling, C; Parker, DM; Dance, DAB; et al. (Public Library of Science, 2021)
Background Burkholderia pseudomallei is a Gram-negative bacterium found in soil and water in many tropical countries. It causes melioidosis, a potentially fatal infection first described in 1911 in Myanmar. Melioidosis is a common cause of sepsis and death in South and South-east Asia, but it is rarely diagnosed in Myanmar. We conducted a nationwide soil study to identify areas where B. pseudomallei is present. Methodology/Principal findings We collected soil samples from 387 locations in all 15 states and regions of Myanmar between September 2017 and June 2019. At each site, three samples were taken at each of three different depths (30, 60 and 90 cm) and were cultured for B. pseudomallei separately, along with a pooled sample from each site (i.e. 10 cultures per site). We used a negative binomial regression model to assess associations between isolation of B. pseudomallei and environmental factors (season, soil depth, soil type, land use and climate zones). B. pseudomallei was isolated in 7 of 15 states and regions. Of the 387 sites, 31 (8%) had one or more positive samples and of the 3,870 samples cultured, 103 (2.7%) tested positive for B. pseudomallei. B. pseudomallei was isolated more frequently during the monsoon season [RR-2.28 (95% CI: 0.70–7.38)] and less in the hot dry season [RR-0.70 (95% CI: 0.19–2.56)] compared to the cool dry season, and in the tropical monsoon climate zone [RR-2.26; 95% CI (0.21–6.21)] compared to the tropical dry winter climate zone. However, these associations were not statistically significant. B. pseudomallei was detected at all three depths and from various soil types (clay, silt and sand). Isolation was higher in agricultural land (2.2%), pasture land (8.5%) and disused land (5.8%) than in residential land (0.4%), but these differences were also not significant. Conclusion/Significance This study confirms a widespread distribution of B. pseudomallei in Myanmar. Clinical studies should follow to obtain a better picture of the burden of melioidosis in Myanmar.